Why is the Victimization of Young Latino Adults Higher in New Areas of Settlement? - Xie, Min (Journal of quantitative criminology, 2018)
We used multilevel data from the National Crime Victimization Survey (NCVS) to identify factors that account for differences in risk of violent victimization among young Latino adults in new and traditional settlement areas.